In Search of Participation: A Study of Some Successful Companies - Portis, Bernard (Relations industrielles / Industrial Relations, 1995)
The article reviews the book, "In Search of Participation: A Study of Some Successful Companies," by J.S. Sodi, Rama J. Joshi, H.V.V. Chellappa, S. Masilamani, Sarita A. Kalia, and Harinda Sanhu.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employee involvement; Employees; Labor Unions; Labor relations; Participatory management; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z